Speed-sensorless Control of Induction Motor Experience on Metro Vehicles - MEI Wen-qing; LIU Yong; GAN Wei-wei (机车电传动)
Based on the principle of induction motor speed estimation, the stability of the estimation algorithm was analyzed, as well as the influence of voltage error and stator resistance error in motor model on speed estimation at very low speed condition in subway traction applications. Stator resistance online correction and voltage error online compensation based on inverter model was used for reducing the speed estimation error and improving the speed estimation accuracy at very low speed condition. Simulation and experiment verified the proposal to meet the requirement of metro vehicle running.